Perubahan Kebiasaan Masyarakat pada Masa Pandemi Covid-19 di Pamijahan Bogor - Rukiat Rukiat; Maturidi Maturidi (Fakultas Syariah IAIN Laa Roiba Bogor, 2021)
This research aims at how changes in people's habits during the Covid-19 pandemic in Kp. Segog, considering there are changes in habits that occur in society at this time. So that people are advised to wear masks, wash their hands and keep their distance and maintain a clean lifestyle. In this study, researchers tried to find steps in a clean lifestyle and inhibiting factors from changing habits in the kp community. Segog. The method used is a case study through interviews using a list of questions. Respondents for this study were people in Kp. Segog. The hope of this researcher can provide inspiration for the community, or for researchers and readers in general. As an additional reference that is used by the wider community. Keywords: Change, Habit, Covid-19.